Penggunaan Teleedukasi untuk Meningkatkan Pengetahuan Manajemen Terapi Asma : A Narrative Review - Margarita, Serli; Sudaryanto, Agus (STIKES Suaka Insan, 2023)
Asthma is a chronic respiratory tract disease characterized by shortness of breath due to inflammation and narrowing of the airways. Asthma can affect all age groups, both young and old. Providing teleeducation facilitates the education process remotely by utilizing information technology and telecommunications. This research aims to conduct a literature study on whether telehealth for people with asthma can increase knowledge after using the applications that have been used. The method used in this research was a literature review study of published journal articles. Database search sources used Pubmed, DOAJ, Google Scholar, and Scopus. The articles were in English and Indonesian and have been published in the last five years. Five articles that have gone through the selection process show varying results regarding the use of teleeducation in managing asthma therapy. Through these five articles, it is known that telehealth has succeeded in increasing knowledge and reasonable asthma control if done routinely. Keywords: telehealth, asthma, asthma management, asthma knowledge and control.